Vertebral artery hypoplasia – diagnostic criteria based on the haemodynamics of the vertebro-basilar circulation - Mysior, Marek; Majos, Agata; Stefańczyk, Ludomir (Menopause Review/Przegląd Menopauzalny, 2007)
Objective: Vertebral hypoplasia is a frequently encountered anatomical anomaly. Although diagnosed by morphological criteria, the limiting diameter of the hypoplastic artery and the degree of side-to-side asymmetry have not been settled unequivocally. We attempted to correlate the diameters of the vertebral arteries with haemodynamic criteria of hypoplasia. Material and methods: 113 healthy volunteers underwent ultrasonography and angio-MR. Cases of vessel tortuosity, significant atherosclerotic lesions and anatomical anomalies were excluded. Then based on diameters of vertebral arteries and flow velocities the flow volume was calculated. Patients were divided into four groups according to the diameter side-to-side asymmetry. The impact of the diameter of the narrower artery and the side-to-side asymmetry on the flow volume was examined. Based on the literature the threshold value of flow volume for the hypoplastic artery was settled at 10% of the total vertebral flow volume. The haemodynamic criterion so defined responded to the arteries less than or equal to 2 mm (the average flow volume ratio 8%, range 2-23%, SD 6%) or the arteries where the diameter difference between sides was twofold (the average flow volume ratio 8%, range 2-15%, SD 4%). Results: The most appropriate morphological criterion of hypoplasia appeared to be the side-to-side asymmetry 2:1 (sensitivity 86%, specificity 96%), followed by the diameter of the narrower artery 2 mm or less (sensitivity 71%, specificity 98%).